2010
DOI: 10.1007/s00265-010-1117-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced recombination and the mechanism of evolvability

Abstract: 16The concept of evolvability is controversial. To some, it is simply a measure of the standing genetic 2 17 variation in a population and can be captured by the narrowsense heritability (h ). To others, 18 evolvability refers to the capacity to generate heritable phenotypic variation. Many scientists, 19 including Darwin, have argued that environmental variation can generate heritable phenotypic 20 variation. However, their theories have been difficult to test. Recent theory on the evolution of sex 21 and rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 63 publications
2
48
1
Order By: Relevance
“…Our data have clearly shown that environmental stress can indeed increase the recombination rate in some stress‐treated individuals, although not all of the offspring whose parent was treated by stress showed a higher number of crossover events (Table ); this is consistent with previous expectations and reports indicating that environmental variations can contribute to evolution through the generation of novel heritable variations via meiotic and somatic recombination (Darwin, ; Puchta et al ., ; Lucht et al ., ; Kovalchuk et al ., ; Molinier et al ., ; Zhang, ; Zhong & Priest, ; Kerstes et al ., ; Puchta & Hohn, ). Interestingly, not all of the stress‐treated individuals have a greater number of crossover events, and only a 1.5‐fold higher recombination rate was found in individuals with the highest recombination rate (52) compared with the average rate (34) (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data have clearly shown that environmental stress can indeed increase the recombination rate in some stress‐treated individuals, although not all of the offspring whose parent was treated by stress showed a higher number of crossover events (Table ); this is consistent with previous expectations and reports indicating that environmental variations can contribute to evolution through the generation of novel heritable variations via meiotic and somatic recombination (Darwin, ; Puchta et al ., ; Lucht et al ., ; Kovalchuk et al ., ; Molinier et al ., ; Zhang, ; Zhong & Priest, ; Kerstes et al ., ; Puchta & Hohn, ). Interestingly, not all of the stress‐treated individuals have a greater number of crossover events, and only a 1.5‐fold higher recombination rate was found in individuals with the highest recombination rate (52) compared with the average rate (34) (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have argued that environmental variations may contribute to evolution through the generation of novel heritable variations via adaptive mutations and/or recombination (Darwin, ; Zhang, ). In addition, a number of studies have shown that many abiotic and biotic factors, such as high salinity, UV irradiation, temperature and pathogen attack, etc., can directly increase somatic recombination, a finding which has been confirmed by the detection of marker transgene‐dependent Arabidopsis lines with imposed stress treatment (Puchta et al ., ; Lucht et al ., ; Kovalchuk et al ., ; Molinier et al ., ; Francis et al ., ; Zhong & Priest, ; Kerstes et al ., ; Puchta & Hohn, ). Moreover, in Drosophila , hot and cold temperatures can also induce higher recombination rates (Smith, ).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of Fitness associated dispersal is part of the more general concept of fitness-associated genetic variation generated through mutation [70,71], recombination in a mixed population [55,72,73], and in particular costly variation, such as condition-dependent sex [56,57,74]. The marked difference between condition-dependent sex and FAD is that, in condition-dependent sex, individuals that do not meet the conditions to reproduce sexually produce offspring that are identical to themselves.…”
Section: Discussionmentioning
confidence: 99%
“…In flies, a negative relationship between fitness and recombination rate was observed for heat and pathogen stress, but not for mating or cold stress [80][81][82], and deleterious mutations have been shown to alter the recombination rate, but not in a consistent way [83].…”
Section: Generalization: Condition-dependent Variationmentioning
confidence: 99%